Increased COX‐2 after ureter obstruction attenuates fibrosis and is associated with EP2 receptor upregulation in mouse and human kidney. (20th May 2022) - Tofteng, Signe S.; Nilsson, Line; Mogensen, Amalie K.; Nørregaard, Rikke; Nüsing, Rolf; Diatchikhine, Mikhail; Lund, Lars; Bistrup, Claus; Jensen, Boye L.; Madsen, Kirsten
Abstract: Aim: Cyclooxygenase‐2 (COX‐2) activity protects against oxidative stress and apoptosis early in experimental kidney injury. The present study was designed to test the hypothesis that COX‐2 activity attenuates fibrosis and preserves microvasculature in injured kidney. The murine unilateral ureteral‐obstruction (UUO) model of kidney fibrosis was employed and compared with human nephrectomy tissue with and without chronic hydronephrosis. Methods: Fibrosis and angiogenic markers were quantified in kidney tissue from wild‐type and COX‐2 −/− mice subjected to UUO for 7 days and in human kidney tissue. COX‐enzymes, prostaglandin (PG) synthases, PG receptors, PGE2, and thromboxane were determined in human tissue. Results: COX‐2 immunosignal was observed in interstitial fibroblasts at baseline and after UUO. Fibronectin, collagen I, III, alpha‐smooth muscle actin, and fibroblast specific protein‐1 mRNAs increased significantly more after UUO in COX‐2 −/− vs wild‐type mice. In vitro, fibroblasts from COX‐2 −/− kidneys showed higher matrix synthesis. Compared to control, human hydronephrotic kidneys showed (i) fibrosis, (ii) no significant changes in COX‐2, COX‐1, PGE2 ‐, and prostacyclin synthases, and prostacyclin and thromboxane receptor mRNAs, (iii) increased mRNA and protein of PGE2 ‐EP2 receptor level but unchanged PGE2 tissue concentration, and (iv) two‐ to threefold increased thromboxane synthase mRNA and protein levels, and increased thromboxane B2 tissue concentration in cortex and outer medulla. Conclusion: COX‐2 protects in the early phase against obstruction‐induced fibrosis and maintains angiogenic factors. Increased PGE2 ‐EP2 receptor in obstructed human and murine kidneys could contribute to protection.